PENGARUH LEVERAGE PROFITABILITAS LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR - Mabid Nurdin, Rini Tri Hastuti (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
This study aims to examine the effect of leverage, profitability, liquidity and firm size on return of stock in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2016-2018 period. Sampling techniques using purposive sampling method. Data is processed using Eviews 10.0. This study uses 61 companies within 3 years period and the result using 183 unit sampling. The results of this study indicate that leverage profitability and liquidity have no effect on return of stock, differing with firm size that significantly influence the return of stock.